2019
DOI: 10.1515/pac-2018-1224
|View full text |Cite
|
Sign up to set email alerts
|

Effects mediated by M2 muscarinic orthosteric agonist on cell growth in human neuroblastoma cell lines

Abstract: The role of muscarinic receptors has been largely documented over the past few decades. Recently we demonstrated that the activation of M2 muscarinic receptors arrested cell proliferation and induced apoptosis in glioblastoma and in other tumour types. This paper aims to evaluate the expression of the M2 muscarinic receptor subtypes in different neuroblastoma cell lines and its role in the control of cell proliferation and survival. Neuroblastoma is the most common solid extracranial tumour, appearing during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Moreover, the contribution of muscarinic receptors in tumor progression has also been demonstrated and the use of agonists or antagonists for different cholinergic receptor subtypes is emerging as therapy for different pathologies [11,[26][27][28]. Previously it has been demonstrated the ability of M2 receptor to counteract tumor cell growth and survival both in GBM and in GSCs [16][17][18][19], in neuroblastoma [29] and in urothelial bladder cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the contribution of muscarinic receptors in tumor progression has also been demonstrated and the use of agonists or antagonists for different cholinergic receptor subtypes is emerging as therapy for different pathologies [11,[26][27][28]. Previously it has been demonstrated the ability of M2 receptor to counteract tumor cell growth and survival both in GBM and in GSCs [16][17][18][19], in neuroblastoma [29] and in urothelial bladder cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in neuroblastoma and glioblastoma cell lines, we have also demonstrated that M1 and M3 antagonists, pirenzepine and 4-DAMP, respectively, were not able to counteract APE effects, confirming preferential selectivity of APE for M2 receptor. Moreover, after M2 knockdown by short interference RNA, APE effect was completely abolished [ 16 , 29 , 30 , 31 ]. Finally, it is relevant to note that M4 receptor expression both in rat [ 9 ] and in hSCs appears significantly lower than M2 subtype, at least at transcript level; for this reason, the potential interference of M4 receptors, should be irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…Our works have been focused on the characterization of APE hydrobromide by pharmacological competition studies with M2 antagonists methoctramine or gallamine [ 8 , 17 , 32 ]. Moreover, the silencing of M2 receptors by siRNAs have largely demonstrated the selectivity of APE for M2 receptor in several cell lines (i.e., human glioblastoma, neuroblastoma, and urothelial bladder cell lines [ 16 , 29 , 30 , 31 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we expanded this list including neuroblastoma, focusing our attention on the M2 muscarinic receptor subtype [ 43 ]. What stands out within our research is how selective activation of this receptor can counteract cell proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, via selective activation with the M2 agonist arecaidine propargyl ester (APE), we have observed an arrest of cell proliferation in a dose-dependent manner both in neuroblastoma and neuroepithelioma cell lines. We found that the effect produced by APE is associated with the selective activation of M2 receptors; in fact, by silencing the M2 sub-type, we observed an abolishment of the effects that APE mediated [ 43 ].…”
Section: Introductionmentioning
confidence: 99%